اقتراح إستراتيجية لإعادة الإعمار بعد الكوارث والحروب حالة دراسية استراتيجية اعادة الاعمارفي سورية - الأحمر, جمال; نانو, نغم (Latakia University Journal -Engineering Sciences Series, 2018)
The aim of this study is to prepare a strategy for reconstruction in Syria after war and disaster, through analysis and utilization of global experiences and theoretical materials, in order to be based on scientific and strategic principles that take into account all the components of the urban environment, working to understand the disaster and its causes, Directing reconstruction to be part of the development plans and upgrading the reality for the better, and the preservation of history and heritage and identity, and achieves the elements of sustainability in the reconstruction projects. Strategic objectives of research: In the beginning, it is necessary to define general objectives of this strategy, which form the basic principles and the general determinants that must be based on them. Taking advantage of the previous case studies and the theoretical framework, it seems clear that any reconstruction strategy must be a comprehensive preventive strategy. Sustainable reconstruction This strategy is fully flexible to fit all circumstances and emergencies. The most important objectives of this strategy are: 1 - Prepared for disaster preparedness and risk reduction in Syria either by preventing or increasing effectiveness in facing and mitigating impacts, and strengthening areas of vulnerability in order to improve the efficiency of the urban environment in the face of disasters. 2 - contribute to increase the capabilities of society in the face of disasters and management and dealing with them with awareness and awareness. 3. This strategy aims to achieve comprehensive reconstruction of all aspects of the urban environment in Syria. 4. This strategy ensures the sustainable reconstruction of the urban environment. 5. This strategy will ensure the preservation of Syria's identity, history and national heritage and preserve memory. 6. This strategy ensures the effective participation of all sectors of society at all stages. تهدف هذه الدراسة إلى إعداد إستراتيجية لاعادة الإعمار بعد الحروب والكوارث في سوريا ، من خلال التحليل والاستفادة من التجارب العالمية والمواد النظرية، لكي تكون وفق أسس علمية وإستراتيجية صحيحة تراعي كل مكونات البيئة الحضرية، تعمل على فهم الكارثة واسبابها ومن ثم تعمل على ادارة الكارثة بالشكل الصحيح وتوجيه اعادة الاعمار لكي يكون جزءا من خطط التطوير والارتقاء بالواقع نحو الافضل، ويؤدي الى حفظ التاريخ والتراث والهوية، ويحقق عناصرالاستدامة في مشاريع اعادة الاعمار وفي عمليات الاستعداد التي تسبق الكارثة اصلا. -الأهداف الاستراتيجية للبحث: في البداية لابد من تحديد أهداف عامة لهذه الإستراتيجية تشكل المبادئ الأساسية والمحددات العامة التي يجب أن ترتكز عليها، وبالاستفادة من الحالات الدراسية السابقة والإطار النظري يبدوا واضحا أن أي إستراتيجية لإعادة الأعمار يجب أن تكون إستراتيجية وقائية، شاملة، تندرج ضمن خطط التطوير العامة وتهدف إلى تحقيق إعادة اعمار مستدام وتتعامل هذه الإستراتيجية بمرونة تامة لتتناسب مع كل الظروف والحالات الطارئة ومن أهم أهداف هذه الاستراتيجية: 1-تعمل على الاستعداد لمواجهة الكوارث والحد من المخاطر في سوريا اما بمنعها أو زيادة الفعالية في مواجهتها والتخفيف من آثارها، وتقوية مناطق الضعف من أجل رفع كفائة البيئة الحضرية في مواجهة الكوارث. 2-تساهم في زيادة قدرات المجتمع في مواجهة الكوارث وادارتها والتعامل معها بادراك ووعي. 3- تهدف هذه الاستراتيجية الى تحقيق عمليات اعادة اعمار شاملة لكل جوانب البيئة الحضرية في سوريا. 4- تضمن هذه الاستراتيجية اعادة اعمار مستدام للبيئة الحضرية. 5-تؤدي هذه الاستراتيجية الى ضمان الحفاظ على الهوية والتاريخ والتراث الوطني السوري وتعمل على حفظ الذاكرة. 6- تضمن هذه الاستراتيجية مشاركة فاعلة لكل قطاعات المجتمع في كل مراحلها.